‏ Media Coverage of Al-Jazeera and AlMamlaka Channels of the Russian-Ukrainian War and its Repercussions on the Jordanian Economy: Facebook pages as a Model - Nejadat, Ali; Al-Shalaldeh, Baraa (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to identify the nature of media coverage on the Facebook pages of "Al-Jazeera – Jordan” and “Al-Mamlaka” regarding the repercussions of the Russian-Ukrainian war on the Jordanian economy. Methods: This study is classified as descriptive-analytical research, which relied on the survey methodology within this framework, content analysis was employed. A form was used to analyze the content of all materials included in the studied pages, which consisted of 94 posts from the Al-Mamlaka page and 100 posts from the Al-Jazeera - Jordan page. Results: The study reached several findings, the most important are as follows: The topic of "Agriculture and Food" ranked first among the topics covered by the study’s Facebook pages, accounting for the percentage of 44.8%, followed by the topic of "clothing" for the percentage of 12.3%. The study also revealed that the studied pages relied mostly on preliminary coverage, with a percentage of 87.6%. Conclusion: There is a need for diversity in the use of journalistic arts, including articles and investigations, on social media pages of media outlets to cover crises and wars, and The social networking pages of various media outlets should rely on their own sources to cover the repercussions of wars and global crises on the economy.